Development and characterization of electric field directed preferentially aligned CNT nanocomposites. Issue 1 (2nd January 2019) - Pothnis, Jayaram R.; Gururaja, Suhasini; Kalyanasundaram, Dinesh
Abstract: The present work demonstrates a novel method to preferentially orient carbon nanotubes (CNTs) in an epoxy matrix using a non-uniform electric field. The alignment method is based on the principle of dielectrophoresis. Aligned CNT/epoxy composites containing 0.01, 0.05 and 0.1 wt. % CNTs, respectively were fabricated using the method. The elastic modulus and hardness of the samples evaluated using nanoindentation technique were observed to increase with increasing CNT loading. The tensile strength of nanocomposite samples containing 0.1 wt. % CNTs increased by approximately 27% due to CNT alignment in epoxy matrix.